Pneumatologi Amos Yong dan Eksistensi GBI Rayon-19, Sumatera Barat - Suhartono, Tony; Sitohang, Hendry (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2023)
This journal explores the suitability of the pneumatology of Amos Yong's religionum as a foundation in inter-religious conversations related to the praxis of the existence of GBI Rayon-19, West Sumatra, which is in the midst of the majority of believers in Indonesia, who have experienced trauma due to the burning of places of worship by the masses who did not want any Christian worship in the area. The method used in this research is descriptive narrative sourced from books and journals, as well as interviews with key figures of GBI Rayon-19, West Sumatra. The conclusion of the researcher is that in the end, the pneumatology theology with the praxis of hospitality is appropriate and applicable to the existence of